Effect of organic and inorganic substances on plant growth and survival in khirni (Manilkara hexandra) - Santosh R Barkule; N.Niranjan; Shivaji J Shinde (Current Horticulture, 2025)
The study was carried out to find out the effect of organic and inorganics on growth and survival of khirni (Manilkara hexandra L.) at Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani, during 2023-2024. Among treatment combinations, seeds soaked in cow dung slurry for 24 hr showed better stem diameter (3.18 mm), seedling vigour index I (3122.55) and seedling vigour index II (107.92), survival (93.42 %) and lesser incidence of damping off (6.58 %), whereas seedling height (18.04 cm), number of leaves (9.97), leaf area (21.36 cm2), plant fresh weight (3.09 g) and plant dry weight (1.44 g) were observed best in treatment seeds soaked in GA3 300 ppm for 12 hr.